2015
DOI: 10.1515/amm-2015-0176
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Strain Rate On The Mechanical Properties And Microstructure Of The High-Mn Steel After Dynamic Deformation Tests

Abstract: The paper presents results of dynamic tensile investigations of high-manganese Fe -20 wt.% Mn -3 wt.% Al -3 wt.% Si -0.2 wt.% steel. The research was carried out on a flywheel machine, which enables to perform dynamic tensile tests and impact bending with a linear velocity of the enforcing element in the range of 5÷40 m/s. It was found that the studied steel was characterized by very good mechanical properties. Strength of the tested materials was determined in the static tensile test and dynamic deformation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, the manufacturing technology for such products needs to be developed in a way that minimizes the number of heat treatments. This approach aligns with the global trend favoring technological solutions that reduce energy consumption [21]. However, in some cases, this approach requires continuing the forging process at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, the manufacturing technology for such products needs to be developed in a way that minimizes the number of heat treatments. This approach aligns with the global trend favoring technological solutions that reduce energy consumption [21]. However, in some cases, this approach requires continuing the forging process at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 80%
“…Nowadays, researchers are focused on C-Mn-Si-Al TRIP steels with microadditions such as Nb, Ti, and Mo [4,8,[17][18][19][20][21]28]. It is related to the fact, that these microadditions improve the properties by enhancing the strength and grain refinement [8][9][10][11][12][13][14][15][16][17][18][19]21]. It is well known that the amount of retained austenite was decreasing as a result of plastic deformation [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…TRIP steels with a ferritic matrix usually contain:~0.2% C,~1.5% Mn, and~1.5% Si or 1.5% Al. Manganese stabilizes the austenitic phase and increases the carbon solubility in ferrite [10]. Sugimoto et al [11] reported that the addition of 2 wt.% Mn resulted in obtaining a higher fraction of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of IT engineering tools and numerical methods based on FEM [19][20][21] are used to analyze and optimize industrial forging processes, often combined with thermal imaging measurements as well as microstructural research or dimensional analysis using laser scanners [22,23]. However, it seems that the most information can be obtained from numerical modeling, because such computational packages allow the determination of many physical quantities and other technological parameters that are difficult or even impossible to determine experimentally [24][25][26], and by introducing new functions verified in industrial conditions, they allow for quick the analysis of the entire industrial process, e.g., determining the distribution of temperatures, stresses, forging forces, flow errors of the deformed material, and even defects in forgings and many other technological aspects [27,28].…”
Section: Introductionmentioning
confidence: 99%